Pengaruh Kompetensi Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Badan Pengembangan Sumber Daya Manusia Provinsi Sumatera Utara - Anggi Jati (Jurnal Ekonomi Bisnis Digital, 2023)
This study aims to determine the effect of competence and work discipline on employee performance at the Human Resource Development Board of North Sumatra Province. In this study using multiple analysis techniques that function to determine the effect of two or more independent variables on the dependent variable. This study uses an associative method with a quantitative approach. The population used in this study was 120 respondents from employees who worked at the Human Resources Development Agency for North Sumatra Province.The results of this study indicate that competence has a positive and significant effect on employee performance with a sig. 0.033 < 0.05 and t count 2.158 > t table 1.980. Work discipline has a negative and significant effect on employee performance with a sig. 0.002 < 0.05 and the t value is -3.128 > 1.980. Competence and work discipline have a simultaneous effect on employee performance with a sig. 0.003 <0.05 and the calculated f value is 6.099 > f table 3.07